2015
DOI: 10.1002/2014gl062444
|View full text |Cite
|
Sign up to set email alerts
|

Biomass burning dominates brown carbon absorption in the rural southeastern United States

Abstract: Brown carbon aerosol consists of light-absorbing organic particulate matter with wavelength-dependent absorption. Aerosol optical extinction, absorption, size distributions, and chemical composition were measured in rural Alabama during summer 2013. The field site was well located to examine sources of brown carbon aerosol, with influence by high biogenic organic aerosol concentrations, pollution from two nearby cities, and biomass burning aerosol. We report the optical closure between measured dry aerosol ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
249
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(268 citation statements)
references
References 76 publications
(140 reference statements)
18
249
1
Order By: Relevance
“…Site description and instruments involved during the SOAS campaign are detailed elsewhere (8,(16)(17)(18). Ambient air was continuously drawn with mechanical pumps through two inlets.…”
Section: Methodsmentioning
confidence: 99%
“…Site description and instruments involved during the SOAS campaign are detailed elsewhere (8,(16)(17)(18). Ambient air was continuously drawn with mechanical pumps through two inlets.…”
Section: Methodsmentioning
confidence: 99%
“…at 365 and 405 nm, and contribute approximately 10 % at midvisible wavelengths, e.g. at 532 nm (Bahadur et al, 2012;Lack et al, 2012b;Washenfelder et al, 2015;Nakayama et al, 2014). During an agricultural waste burning event, BrC aerosol could contribute more than 65 % of light absorption at 370 nm and 15 % at a mid-wavelength (Favez et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Potential sources of BrC include emissions from biomass burning (Kirchstetter et al, 2004;Moosmüller et al, 2009;Chen and Bond, 2010;Lack et al, 2012a;Saleh et al, 2014;Washenfelder et al, 2015); incomplete combustion of fossil fuels, especially coal (Bond, 2001;Yang et al, 2009;Olson et al, 2015); and secondary organic aerosols (Saleh et al, 2013;Zhang et al, 2013;Lin et al, 2015). There exists significant uncertainty concerning the relative contribution of each of these source types to total BrC concentrations, but several studies have identified biomass burning as a potentially significant source (Washenfelder et al, 2015;McMeeking et al, 2014;Lack et al, 2012a).…”
mentioning
confidence: 99%
“…There exists significant uncertainty concerning the relative contribution of each of these source types to total BrC concentrations, but several studies have identified biomass burning as a potentially significant source (Washenfelder et al, 2015;McMeeking et al, 2014;Lack et al, 2012a). Open biomass burning (BB) is one of the largest global sources of BC and organic carbon (OC), and biomass burning emissions have a significant direct effect on the Earth's radiative balance (Bond et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation